Indonesian Language Destroyers Applied by Public Figures Through Social Media - Amran, Ali (English Teaching and Linguistics Journal (ETLiJ), 2024)
This research aims to investigate why Indonesian public figures mix some English words or phrases into Indonesian language when they are having conversation in social medias, like on TV, You Tube channels. The researcher also wants to professionally discover some negative effects towards the grammar, meanings of those mixing (Indonesian-English) statements conducted by public figures. All language experts agree that every language has its own standard rules to follow. For example, when we write, “There is three problems in this statement”. It is grammatically non-standard English. The verb “is” must be changed with “are” and the word “problem” must plus “s”. It becomes “There are three problems in this statement”. Let alone when we mix some English words or phrases into Indonesian language. One example, “Saya hanya mau sharing--haring informasi”. The questions are, 1). Does this sentence make any sense?  2). Does the user know the meaning of the word sharing? 3). Does this sentence produce the standard grammar either in English or in Indonesian language? The standard one is “Saya hanya mau berbagi informasi”. Besides, the words “sharing-sharing” is not available and applicable in English.  The researcher’s opinion is mixing the words into different languages is called “language destroyers”. It is expected that this study is beneficial for those language teachers, lecturers and public figures and also hoped that in the future language “destroyers” less and less exist.